Razlike u motorikim sposobnostima rukometaša razlicitog ranga natjecanja - Separovic, V.; Uzieanin, E.; Srsen, I. (Sportski Logos, 2015)
Basic goal of this research was to determine the level of certain motor skills of handball players playing for handball teams RK Metkovic 1963 and RK Opuzen, and on the basis of statistical processing and interpretation of obtained results to answer the following question: Is there a statistically significant difference between motor skills of handball players playing for handball teams RK Opuzen and RK Metkovic 1963, in which tests they show the biggest difference on statistically significant level and in favor of which team? The research was conducted on the sample including 26 handball players, 13 from handball team RK Opuzen and 13 from handball team RK Metkovic 1963. All players were between 18 - 35 years old. Sample of variables consisted of 9 motor skill tests, 2 tests of situational-motor skills in handball and 2 measurements of morphological characteristics. Results obtained through independent samples T-test showed that players from RK Metkovic 1964 and RK Opuzen showed statistically significant differences in variables MRESKL (pushups), MREPTL (lifting body from the lying position), MFE20V (20 m sprint from medium start), SKOTBL (defensive movement in the triangle without ball), SBIDP (lateral and deep movement) and MAGKUS (side steps). Determined differences between variables for the assessment of motor skills provide clear guidelines for planning the work on improving efficiency of motor skill programs as the starting point for the improvement of handball technique and tactics and eventually in the accomplishment of defined competitive goals.